A study on factors affecting newborn weight and large for gestational age newborns in non-diabetic mothers: The role of maternal serum triglycerides - Hussain, Nik Hazlina Nik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Introduction: Triglycerides have been shown to be a biochemical predictor of newborn weight and risk of large for gestational age (LGA) in a few previous small studies. The objective of this study is to ascertain whether mid-pregnancy fasting serum triglycerides can predict the risk of developing LGA and newborn weight in non-diabetic pregnant mothers. Methodology Universal sampling of pregnant mothers attending the antenatal clinic at the Hospital Universiti Sains Malaysia (HUSM) and nearby clinics between 24 to 32 weeks gestation was carried out between December 2003 and July 2004. Expectant mothers were screened for exclusion criteria including diabetes, hypertension, preeclampsia, fetal anomaly and multiple gestations. Those who were sure of dates and consented for the study were enrolled. Modified ora.l glucose tolerance test (MOGTT) was performed and fasting serum triglycerides and total cholesterol were analysed. The subjects were followed up at delivery when the period of gestation, the birth weight and the sex of newborn were noted. The correlations of the variables with newborn weight were tested and multiple linear regressions were used to find the associations. Bivariate logistic regression was used to look at the association of LGA newborn and the variables including triglycerides which were divided into two groups. The associations of the two groups of triglycerides and fasting plasma glucose (FPG) with the incidence of LGA were tested in cross tabulations. Results: A total of 310 subjects were enrolled and 267 completed data were analyzed, 246 were normal glucose tolerant (NGT) and 21 impaired glucose tolerant (IGT). The incidence of IGT in this study was 7.9%. In NGT, triglycerides correlated poorly (r-0.14, p=0.03) with newborn weight while maternal body mass index (BMI) (r-0.30, p<0.001) and FPG (r-0.28, p<0.027) were the only two variables moderately correlated with newborn weight after adjustment of the gestation and gender of the newborn. FPG (OR 3, p=0.027), high triglycerides value (>2.78mmoi/L) (p=0.039) and 2 hours postprandial plasma glucose (HPPPG) (p=0.044) were associated with risk of LGA newborn. With high triglycerides (>2.78mmoi/L) and FPG (>4.3mmoi/L), risk of getting LGA was 31.8o/o (p<0.001). Conclusions: In NGT subjects, mid-pregnancy high FPG and high triglycerides value could be used to predict risk of getting LGA newborn.